Therapist experiences of congruence in school-based counselling - Scott, Krystal; Blundell, Peter; Dougan, Lesley (European Journal for Qualitative Research in Psychotherapy, 2023)
Congruence is a key counselling concept, perhaps the most important of the therapist provided conditions (Rogers, 1967). Whilst literature on congruence and its use within the therapeutic relationship is rich, there is a lack of research exploring how counsellors understand, experience and offer congruence with children in school-based counselling programmes – the focus of this study. Using hermeneutic phenomenology as a philosophical base, semi-structured interviews were conducted with three person-centred counsellors and one integrative counsellor who currently work with children in a school-based counselling service. The data was analysed using interpretative phenomenological analysis (IPA) resulting in two superordinate themes: Intrapersonal Congruence and Navigating Multiple Terrains. This study suggests that congruence with children in school-based counselling is best understood as an intrapersonal phenomenon. Key findings indicate that conscious non-disclosure of therapist process was central to work with children. This served to protect and enhance the therapeutic relationship. Other findings suggest that the presence of certain aspects of therapist self in the room can impact upon congruence. Therapist personal self-disclosure was essential in facilitating a strong therapeutic alliance with children for one research participant and a central aspect of his experience of congruence with children. Lack of clarity around the unique roles and responsibilities of working in a school setting as a counsellor affected the way therapists experience and offer congruence with children and young people. Implications for training and practice are considered.